2022
DOI: 10.1186/s12987-022-00324-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neuroinflammation in hydrocephalus after intraventricular hemorrhage: a review

Abstract: Intraventricular hemorrhage (IVH) is a significant cause of morbidity and mortality in both neonatal and adult populations. IVH not only causes immediate damage to surrounding structures by way of mass effect and elevated intracranial pressure; the subsequent inflammation causes additional brain injury and edema. Of those neonates who experience severe IVH, 25–30% will go on to develop post-hemorrhagic hydrocephalus (PHH). PHH places neonates and adults at risk for white matter injury, seizures, and death. Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 187 publications
0
33
0
Order By: Relevance
“…Despite NPH has been first described in the 1960s [4], its pathophysiology has been only partly explained. In particular, in recent years several studies have highlighted the role of neuro-inflammation in the genesis of NPH, both in the idiopathic [5][6][7][8] and in post-hemorrhagic secondary forms [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite NPH has been first described in the 1960s [4], its pathophysiology has been only partly explained. In particular, in recent years several studies have highlighted the role of neuro-inflammation in the genesis of NPH, both in the idiopathic [5][6][7][8] and in post-hemorrhagic secondary forms [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia results in dramatic changes in the morphology, density, and function of branched microglia, including processes such as cell body enlargement, debranching, and cell wall thickening. It eventually becomes "amebic", produces inflammatory proteins, and undergoes changes in proliferation, migration, and phagocytosis (88). Because m i c r o g l i a a n d b l o o d -m i g r a t i n g m a c r o p h a g e s a r e morphologically indistinguishable and perform similar functions, they are represented as microglia/macrophages in many studies.…”
Section: Activation Of Microglia and Activation Recruitment And Polar...mentioning
confidence: 99%
“…Blood products in the ventricles are suspected to be responsible for the dilatation and Miller et al [ 129 ] have shown that hemoglobin injected into the ventricles of neonatal rats can induce hydrocephalus. Neuroinflammation is also involved in IVH-induced hydrocephalus (reviewed in [ 130 ]). Inflammatory markers in the CSF are associated with hypersecretion of CSF via hyperactivity of choroid plexus transporters, raising the potential for future pharmaceutical treatment [ 43 ].…”
Section: Neurological Disordersmentioning
confidence: 99%